Impact fatigue analysis on welded pipelines of hydrocarbon transport (2020)
Studies of response on pipelines under repetitive action of dynamic forces are limited. For that reason, the objective of this investigation is to determine the behavior of fatigue and fracture in welded joints of pipelines under cyclic load and impact load conditions with the quasi-static and dynamic material characterization of fracture toughness. This work focuses especially on the analysis of repetitive low energy impacts loads which cause a progressive loss of carrying capacity in the pipes and final failure. The proposed experimentation is composed of quasi-static and dynamic characterization of material through tests of crack mount opening displacement (CMOD) under plane strain condition and unloading compliance, fatigue under sinusoidal constant load amplitude, impact fatigue crack propagation (Dynamic CMOD) by drop weight test (DWT), and energy absorption analysis in single edge notch bending (SENB) configuration followed by a metallographic and fractographic inspection. Besides, an X-ray inspection test and uniaxial tensile test were performed as a complement to the experimentation to validate the material meets the minimum requirements given by the API 5L Specification for Line Pipe standard in terms of mechanical properties and quality in the welding.